Neoproterozoic fluvial succession of the Ramgiri Formation, Pranhita–Godavari Valley, India: implications for sheet-braided versus deep channelized models of pre-vegetation fluvial systems - Chakraborty, Tapan; Taral, Suchana (Frontiers in Earth Science, 2025)
In recent years, deposits of deep channelized fluvial systems have been documented in some pre-Silurian successions, casting doubts on the exclusive sheet-braided models of pre-vegetational fluvial sedimentation. In this study, we explore the Neoproterozoic Ramgiri Formation to (i) understand the surface processes in a pre-vegetation fluvial system, (ii) examine the existence of sheet-braided or channelized architecture in this succession, and (iii) identify possible process controls that might have resulted in either a sheet braided or channelized architecture in these deposits. This study examines a ∼50 km-long transect of the outcrop belt, subdividing the succession into ten facies and three facies associations, supported by sedimentological logs and paleocurrent data. Facies association I consists of sheet-like units of weakly channelized, stratified pebble-coble conglomerate alternating with trough cross-stratified pebbly sandstone. Facies association II consists of comparatively finer, pebbly, coarse-grained, sheet sandstones with small trough cross-strata, capped by thin mudstones. Both associations show an abundance of dm-thick, mass flow or hyperconcentrated flow deposits. The regional paleocurrent patterns of these two associations are dominantly NE-trending, transverse to the basin axis, representing proximal (FA I) and distal (FA II) megafan deposits. Facies association III, in contrast, contains >3 m deep channel scours, thick simple and compound bedforms, and bars. The overall paleoflow of FA III is toward the SE, parallel to the basin axis, and represents deposition from a lower-gradient, perennial, sandy braided river. We infer that the flows were sheet-like on the megafan because of its steeper gradient, resulting in flow attenuation and widening on a non-cohesive substrate, whereas the lower-gradient, higher-discharge axial drainage of FA III gave rise to deeper channel bedforms similar to the Phanerozoic fluvial deposit. The geophysical and tectonic data indicate that the Godavari basin developed as a half-graben with an active normal fault on its NE margin and a roll-over anticline on the SW margin. The Ramgiri megafans developed on the roll-over margin, and the adjacent low-gradient axial basin plain was occupied by deeper channels, resulting in the simultaneous development of contrasting fluvial architectures.